Antibody response to a 33 kDa cysteine protease of Trypanosoma congolense: Relationship to 'trypanotolerance' in cattle - Authié, Edith; Duvallet, G.; Robertson, C.; Williams, D.J.L. (Wiley, 1993)
A cysteine protease of Trypanosoma congolense (congopain) elicited IgG1 antibodies in those cattle which exhibited a degree of resistance to disease during experimental infections (Authié et al. 1992, 1993). The aim of the present study was to investigate further the association between anti‐congopain antibodies and resistance to trypanosomiasis, and to provide a lead into the mechanisms responsible for the differential responses to congopain in cattle. Isotype characteristics and kinetics of the antibody response to congopain were studied in three N'Dama (trypanoresistant) and three Boran (susceptible) cattle during primary infection with T. congolense ILNat 3.1. In both groups an IgM response to congopain was elicited, thus demonstrating that congopain is antigenic in both types of cattle. Most of the IgM appeared to be incorporated into immune complexes. IgG was detected as free antibody; IgG1 but not IgG2 was detected. All three N'Dama, but none of the three Boran cattle, mounted a significant IgG response to congopain. Sera from 70 primary‐infected cattle belonging to five breeds of differing susceptibility were tested for their reactivity to congopain. High levels of IgG to congopain were observed in the two trypanotolerant breeds, whereas the three susceptible breeds had lower levels of these antibodies. Crosses between N'Dama and Boran cattle, which exhibit an intermediate susceptibility, had intermediate levels of antibodies. Thus, the results from experimental infections confirmed our initial observations. However, under natural tsetse challenge, repeated infections and trypanocidal treatments in Zebu cattle stimulated as high anti‐congopain antibody levels as in non‐treated trypanotolerant taurine cattle.